2014
DOI: 10.1108/jap-03-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding elder abuse and neglect in aging Chinese immigrants in Canada

Abstract: Purpose -The purpose of this paper is to review and discuss existing literature and available research findings related to understanding elder abuse and neglect in culturally diverse communities, particularly the Chinese immigrant community in Canada. The conceptual understandings of elder abuse are examined, based upon the socio-cultural context and challenges faced by aging Chinese immigrants. Design/methodology/approach -Previous literature and research publications related to elder abuse and neglect relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…There are evidences that older people like to settle finally in the set up conducive for older adults. However, it has been observed that the older adults may be abused in domestic as well as institutional setting (Lai et al, 2014 ). In most of the cases it is exercised by the person on whom he or she relies for physical and psychological support.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are evidences that older people like to settle finally in the set up conducive for older adults. However, it has been observed that the older adults may be abused in domestic as well as institutional setting (Lai et al, 2014 ). In most of the cases it is exercised by the person on whom he or she relies for physical and psychological support.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest that the abuse towards women is high (Lai, 2004 ; Lai & Chau, 2007 ). However, in most of the cases it is in the cases of intimate partner abuse (Lai et al, 2014 ). Moreover, the age of the person is also one of the responsible factors for increased chances of elder abuse.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations